Clinical features and prognostic factors of patients with chordoma in the spine: a retrospective analysis of 153 patients in a single center. Issue 5 (8th December 2014) - Meng, Tong; Yin, Huabin; Li, Bo; Li, Zhenxi; Xu, Wei; Zhou, Wang; Cheng, Mo; Wang, Jing; Zhou, Lei; Yang, Xinghai; Liu, Tielong; Yan, Wangjun; et al.
Abstract: Background: Chordoma in the spine is relatively rare, and minimal information has been published in the literature regarding this subject. Moreover, there are controversies over prognostic factors of this disease. Methods: A retrospective analysis of chordoma in the spine was performed by survival analysis. Local relapse-free survival (LRFS) and overall survival (OS) were analyzed from the date of surgery to the date of local recurrence and death. The LRFS and OS rates were estimated using the Kaplan–Meier method to identify potential prognostic factors. Factors with P values ≤ .1 were subjected to multivariate analysis by Cox regression analysis. P values ≤ .05 were considered statistically significant. Results: A total of 153 patients with spinal chordoma were included in the study. The mean follow-up period was 72.0 months (range, 1–279 months). Local recurrence was detected in 51 cases after initial surgery in our center, while death occurred in 42 cases. The statistical analysis suggested that tumor location of C3–L5, dedifferentiated chordoma, preoperative Frankel scores A–C, and total spondylectomy were independent prognostic factors for LRFS. In addition, total en bloc spondylectomy and Karnofsky' performance status (KPS) ≥ 80% were favorable factors for OS. Conclusions: Total spondylectomy, by either en bloc or piecemeal method, could significantly reduce LRFS for spinal chordoma. Location of C3–L5 is a favorable factor for LRFS, while dedifferentiated subtype and preoperative Frankel scores A–C are adverse prognostic factors. In addition, total en bloc spondylectomy and KPS ≥ 80% significantly improve overall survival of patients with spinal chordoma.